2018
DOI: 10.1101/365890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Genetic Landscape of Diamond-Blackfan Anemia

Abstract: Diamond-Blackfan anemia (DBA) is a rare bone marrow failure disorder that affects 1 in 100,000 to 200,000 live births and has been associated with mutations in components of the ribosome. In order to characterize the genetic landscape of this genetically heterogeneous disorder, we recruited a cohort of 472 individuals with a clinical diagnosis of DBA and performed whole exome sequencing (WES). Overall, we identified rare and predicted damaging mutations in likely causal genes for 78% of individuals. The majori… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
96
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(107 citation statements)
references
References 80 publications
3
96
1
7
Order By: Relevance
“…Ribosomal protein (RP) haploinsufficiency is the major cause of DBA and at least 19 genes that affect ribosomal biogenesis have been found to be linked to DBA 4 . Through whole-exome sequencing in patients in DBA, several rare mutations in previously unreported RP genes were found 4,5 , and one such mutation is a novel nonsynonymous mutation (p.L51S) in rpl18 analysis of pre-rRNA processing in patients' cells showed an increase in the 36S ribosomal subunit compared with controls, indicating a defect in pre-rRNA processing 6 . However, no in vivo, organismal level research has elucidated the function of rpl18 in embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomal protein (RP) haploinsufficiency is the major cause of DBA and at least 19 genes that affect ribosomal biogenesis have been found to be linked to DBA 4 . Through whole-exome sequencing in patients in DBA, several rare mutations in previously unreported RP genes were found 4,5 , and one such mutation is a novel nonsynonymous mutation (p.L51S) in rpl18 analysis of pre-rRNA processing in patients' cells showed an increase in the 36S ribosomal subunit compared with controls, indicating a defect in pre-rRNA processing 6 . However, no in vivo, organismal level research has elucidated the function of rpl18 in embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…Within the large variety of endocrine issues in DBA, recent clinical observational studies suggest that women with DBA have an increased incidence of delayed puberty, irregular menstrual cycles and decreased fertility (Lanes et al, 2000;Tufano et al, 2014;Lahoti et al, 2016). It has been demonstrated that pregnancies in DBA are decreased in numbers and more frequently complicated compared to the general population, reflected by a high prevalence of spontaneous abortions (Faivre et al, 2006;Alter et al, 2010).…”
Section: Fertility/pregnancymentioning
confidence: 99%
“…Летальність серед пацієнтів з тяжкими термічними ураженнями залишається високою навіть у спеціалізованих стаціонарах. Особливо високою вона є при критичних (понад 30 % поверхні тіла) та надкритичних (понад 50 %) глибоких опіках [13,22,29].…”
unclassified
“…Перебіг опікової хвороби залежить від цілої низки факторів: тяжкості опікової травми, віку постраждалого, строків початку лікування, наявності супутніх захворювань. Тяжкість опікової травми визначається, у свою чергу, площею опікових ран та масштабами глибокого пошкодження шкірного покриву [7,24,21,22].…”
unclassified
See 1 more Smart Citation